Exploring the roles of MACIT and multiplexin collagens in stem cells and cancer. (May 2020) - Izzi, Valerio; Heljasvaara, Ritva; Heikkinen, Anne; Karppinen, Sanna-Maria; Koivunen, Jarkko; Pihlajaniemi, Taina
Abstract: The extracellular matrix (ECM) is ubiquitously involved in neoplastic transformation, tumour growth and metastatic dissemination, and the interplay between tumour and stromal cells and the ECM is now considered crucial for the formation of a tumour-supporting microenvironment. The 28 different collagens (Col) form a major ECM protein family and display extraordinary functional diversity in tissue homeostasis as well as in pathological conditions, with functions ranging from structural support for tissues to regulatory binding activities and storage of biologically active cryptic domains releasable through ECM proteolysis. Two subfamilies of collagens, namely the plasma membrane-associated collagens with interrupted triple-helices (MACITs, including ColXIII, ColXXIII and ColXXV) and the basement membrane-associated collagens with multiple triple-helix domains with interruptions (multiplexins, including ColXV and ColXVIII), have highly interesting regulatory functions in tissue and organ development, as well as in various diseases, including cancer. An increasing, albeit yet sparse, data suggest that these collagens play crucial roles in conveying regulatory signals from the extracellular space to cells. We summarize here the current knowledge about MACITs and multiplexins as regulators of stemness and oncogenic processes, as well as their roles in influencing cell fate decisions in healthy and cancerous tissues. In addition, we present a bioinformatic analysis of the impacts of MACITs and multiplexins transcript levels on the prognosis of patients representing a wide array of malignant diseases, to aid future diagnostic and therapeutic efforts.